In vivo metabolism of N-phenyl-N '-(3,5-dimethylpyrazole-4-yl) thiourea in rats - (:unkn) unknown (MEDECINE ET HYGIENE, 2003)
Thiourea derivatives have been shown to posses several biological activities. Therefore a series of N-substituted -N'-(3,5-di/1,3,5-trimethylpyrazole-4-yl)thioureas were synthesized and the antitubercular and anticonvulsant activities were studied. Among the new compounds, N-phenyl-N'-(3,5-dimethylpyrazole-4-yl)thiourea (S) was demonstrated to have remarkable anticonvulsant activity. In this study, S was selected as a model compound and the in vivo metabolic pathway in rats was investigated. The substrate was given intraperitoneally (50 mg/kg) and blood samples were collected at 0, 1, 2, 4, 8, 12, 24 and 48 h. The substrate and its potential metabolites were separated using HPLC on reverse phase system. The substrate was detected at all times with small quantity of metabolites.
Keywords: thiourea; in vivo metabolism; rats; REVERSE-TRANSCRIPTASE INHIBITORS; HUMAN IMMUNODEFICIENCY VIRUS-1; PETT COMPOUNDS; DERIVATIVES; RESISTANT; ANALOGS